Study on the Mechanical Properties and Degradation Mechanisms of Damaged Rock Under the Influence of Liquid Saturation - Bowen Wu; Jucai Chang; Jianbiao Bai; Chao Qi; Dingchao Chen (Applied Sciences, 2025)
To investigate the degradation mechanisms of the surrounding rock in abandoned mine roadways used for oil storage, this study combined uniaxial compression tests with digital image correlation (DIC), scanning electron microscopy (SEM), and other techniques to analyze the evolution of the rock mechanical properties under the coupled effects of oil–water soaking and initial damage. The results indicate that oil–water soaking induces the loss of silicon elements and the deterioration of microstructure, leading to surface peeling, crack propagation, and increased porosity of the sample. The compressive strength decreases linearly with the soaking time. Acoustic emission (AE) monitoring showed that after 24 h of soaking, the maximum ringing count rate and cumulative count decreased by 81.7% and 80.4%, respectively, compared to the dry state. As the liquid saturation increases, the failure mode transitions from tension dominated to shear failure. The synergistic effect of initial damage and oil–water erosion weakens the rock’s energy storage capacity, with the energy storage limit decreasing by 45.6%, leading to reduced resistance to external forces.